ŹRÓDŁA PRZEWAG KONKURENCYJNYCH PRZEDSIĘBIORSTWA W GOSPODARCE OTWARTEJ - Śliwiński, Rafał (Wydział Prawa i Administracji UAM, 1999)
Economic transformation in Poland do force enterprises to function under conditions o f intensive competition. Simply for to survive - Polish firms must in a very short time learn and assimilate new rules if the game, based on competition. When wanting to start any effective competition one must first of all get acquainted with sources of competitive advantages of foreign firms - taking into consideration that the experience of the latter is much bigger - and being done that functional strategies are the germ o f any such advantages - the article focuses on these strategies and discusses with more details some particular strategies of this kind together with ensuing advantages for a firm. In particular the Author considers functional strategies of marketing divisions, of productions, finances, research and development, staff management and running of information. Within the framework of the above mentioned divisions - there is also an analysis of strategies proper to particular smaller subdivisions with a review of possible competitive advantages for them.
SOURCES OF COMPETITIVE ADVANTAGES OF A FIRM IN OPEN ECONOMIES